RNAseq-differentiated gene expression profile of people living with HTLV-1 in the Brazilian Amazon region: a pilot study - Soares Pereira, Leonn Mende; Ferreira, Rafaella do Nascimento; Azevedo, Vânia Nakauth; Freitas Queiroz, Maria Alice; Dias Dantas, Carlos Willian; Ramos, Rommel Thiago Jucá; Patroca da Silva, Sandro; da Costa, Carlos Araújo; Sousa, Maisa Silva de; Vieira Cayres Vallinoto, Izaura Maria; Cruz, Ana Cecília Ribeiro; Rosário Vallinoto, Antonio Carlos (Frontiers in RNA Research, 2024)
In this study, we aimed investigated the differential gene expression profiles of samples from uninfected individuals (control group) and study groups of asymptomatic human T-lymphotropic virus 1 (HTLV-1) carriers and patients with HTLV-1-associated myelopathy (HAM) by exploratory RNA sequencing (RNA-Seq) analysis. The gene expression profiles of individuals in the asymptomatic group were represented by 3 genes, most associated with cell cycle regulation. The gene expression profiles of individuals in the HAM group were represented by 12 genes, the majority of which are associated with the immune response. The HLA-A gene and the non-coding RNA LINC02470 were upregulated in the asymptomatic and HAM groups. The HLA-DQB1 and HLA-C genes were downregulated in the asymptomatic and HAM groups. In this pilot study, although limited in terms of methodological rigor, we showed differential gene expression profiles in different clinical groups of HTLV-1 infection. However, further studies are needed to confirm these findings.